2022
DOI: 10.3389/fmicb.2022.889551
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics Provides Insights Into Genetic Diversity of Clostridium tyrobutyricum and Potential Implications for Late Blowing Defects in Cheese

Abstract: Clostridium tyrobutyricum has been recognized as the main cause of late blowing defects (LBD) in cheese leading to considerable economic losses for the dairy industry. Although differences in spoilage ability among strains of this species have been acknowledged, potential links to the genetic diversity and functional traits remain unknown. In the present study, we aimed to investigate and characterize genomic variation, pan-genomic diversity and key traits of C. tyrobutyricum by comparing the genomes of 28 str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 90 publications
1
9
0
Order By: Relevance
“…The valid members of A. hydrophila have been selected for further analysis, and the misidentified strains were excluded. This was based on the threshold value that indicates the presence of the same species of ANI being greater than 94% 22 , 28 . For confirmation of ANI results, the recommended BLAST+ method was utilized to create digital DNA-DNA hybridization (dDDH) values for DNA-DNA hybridization using the Genome-to-Genome Distance Calculator online server (GGDC v3) 29 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The valid members of A. hydrophila have been selected for further analysis, and the misidentified strains were excluded. This was based on the threshold value that indicates the presence of the same species of ANI being greater than 94% 22 , 28 . For confirmation of ANI results, the recommended BLAST+ method was utilized to create digital DNA-DNA hybridization (dDDH) values for DNA-DNA hybridization using the Genome-to-Genome Distance Calculator online server (GGDC v3) 29 .…”
Section: Methodsmentioning
confidence: 99%
“…strains were functionally re-annotated using the Prokka suite, version 1.14.6. The following settings were used to predict the protein-coding genes: -genus Aeromonas -species hydrophila -evalue 1e−09 -coverage 80 -mincontiglen 200) according to Podrzaj et al 28 . Roary 30 was then used to build the core- and pan-genome of Aeromonas spp.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Clostridium species butyricum , sporogenes , and beijerinckii have been associated with LBD ( Klijn et al, 1994 ; Klijn et al, 1995 ; Cocolin et al, 2004 ; Le Bourhis et al, 2007 ; Garde et al, 2011a ; Brändle et al, 2018b ), it is known that Clostridium tyrobutyricum is the main cause of this defect in most cheese types. However, a remarkable degree of phenotypic and genetic diversity has been widely reported among strains of the C. tyrobutyricum species ( Garde et al, 2012 ; Ruusunen et al, 2012 ; Bermudez et al, 2016 ; Burtscher et al, 2020 ; Podrzaj et al, 2020 ; Podrzaj et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, fingerprinting studies demonstrated low similarity of strain FAM25158 to the fingerprints of other C. tyrobutyricum strains ( Burtscher et al, 2020 ). Furthermore, genomic comparison of C. tyrobutyricum strains revealed a distant genetic relationship between strain FAM25158 and 28 C. tyrobutyricum strains ( Podrzaj et al, 2022 ). Therefore, in this study, we aimed to extend the investigation of strain FAM25158 to elucidate its characteristics and assess its significance.…”
Section: Introductionmentioning
confidence: 99%